Effect of Ethanol and IPTG on the Recombinant Jembrana Trans-Activator of Transcriptation Protein Expression - Indriawati, Indriawati; Salfia, Mega; Susanti, R; Margawati, Endang Tri (Biosaintifika: Journal of Biology & Biology Education, 2018)
Jembrana diseases are caused by Jembrana Diseases Virus (JDV). The previous study showed that Jembrana Trans-Activator of Trancriptation (JTAT) recombinant protein is effective as a vaccine for Jembrana diseases. The production of JTAT protein needs to be optimized to obtain a higher amount of vaccine. High expression of JTAT protein will produce a high vaccine product. This study aimed to examine the effect of the addition of ethanol and IPTG in E. coli media on the expression of JTAT recombinant protein. This research was experimental research with factorial RAL design with a variation factor of ethanol and IPTG. Qualitatively, the induction of each IPTG, ethanol and interaction between the two could induce the expression of JTAT protein and could be identified with SDS-PAGE at ±11.8 kDa. Statistically, the induction of IPTG, ethanol and interaction between the two were not significantly different. Qualitative and quantitative data show that ethanol can induce JTAT protein expression. This result can be used as a preliminary study to test the effectiveness of ethanol as a substitute for IPTG in inducing the recombinant protein expression.